2021
DOI: 10.1016/s2468-2667(21)00203-6
|View full text |Cite
|
Sign up to set email alerts
|

Ending tuberculosis in China: health system challenges

Abstract: China has made remarkable progress in reducing tuberculosis cases and deaths during the past three decades; however, it is still far from achieving the targets set out in the WHO End TB Strategy. Since the 2000s, China has tried to transform its vertical tuberculosis control programme led by the Chinese Center for Disease Control and Prevention (CDC) into an integrated system under the collaboration of CDC, tuberculosis-designated hospitals, and primary health centres. Such a transition has faced many challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 32 publications
1
43
0
1
Order By: Relevance
“…On the one hand, medical staff and animal husbandry practitioners abide by relevant regulations and laws on epidemic prevention in the process of medical treatment, breeding, and sales, and do a good job in environmental disinfection to avoid the spread of MTBC ( 50 ). On the other hand, the government and tuberculosis prevention and control institutions should enhance the subjective perception that MTBC in the environment harms the human and animal health and pay adequate attention to the MTBC in the environment causing tuberculosis ( 60 ). At the national level, the government needs to establish a feasible MTBC monitoring and prevention system in the environment.…”
Section: One Health Prospectsmentioning
confidence: 99%
“…On the one hand, medical staff and animal husbandry practitioners abide by relevant regulations and laws on epidemic prevention in the process of medical treatment, breeding, and sales, and do a good job in environmental disinfection to avoid the spread of MTBC ( 50 ). On the other hand, the government and tuberculosis prevention and control institutions should enhance the subjective perception that MTBC in the environment harms the human and animal health and pay adequate attention to the MTBC in the environment causing tuberculosis ( 60 ). At the national level, the government needs to establish a feasible MTBC monitoring and prevention system in the environment.…”
Section: One Health Prospectsmentioning
confidence: 99%
“…Currently, it is estimated that around 2 billion people are infected with Mtb [5] , which makes TB the leading fatal single infectious disease worldwide [6] . Globally, the severity of TB epidemics differs among countries and regions while China ranked the second among the top 30 high-burden TB countries just behind India, which accounted for 9% of all the TB cases [7] and indicated that China was still far from achieving the targets set out in the WHO End TB Strategy [8] . Thus, it is important to strengthen the national health policy and improve capacities of TB screening, diagnosis and outpatient treatment so as to prevent, control and finally terminate TB infections in China.…”
Section: Introductionmentioning
confidence: 99%
“…The WHO estimated that 9.9 million people fell ill with tuberculosis (TB) worldwide in 2020, and TB is always one of the most important public health concerns in the world. China has the second-highest number of TB cases (8.5%) in the world and is still one of the countries with the highest TB burden (Long et al, 2021). In the past 2 years, the COVID-19 pandemic has caused enormous health, social and economic impacts, including the provision of and access to essential TB services, the number of people diagnosed with TB and the notifications of TB cases through the national disease surveillance systems and TB disease burden (Umubyeyi Nyaruhirira et al, 2022).…”
Section: Introductionmentioning
confidence: 99%